Interdependensi Strategi Pemasaran Terhadap Kinerja Perusahaan (Suatu Penelitian pada Perusahaan Asuransi Indonesia yang sudah Go Public) - Hidayat, Cecep; Putong, Iskandar; Sari, Rini Kurnia (Bina Nusantara University, 2014)
This study aims to analyze the interdependence between the variables of marketing strategy and organizational performance of insurance companies using canonical correlation analysis with multiple multivariate analysis approach. The interdependent correlation value may explain the subgroup which the dominant variable affects other subgroups on the company based on the value of redundancy index. The study population was 9 go public insurance companies when the study was conducted in 2013. Given two exogenous variables, i.e. variables Effectiveness Strategy (STRAEFEK) and Efficiency Strategy (STRATEFIS). Endogenous variable is the Debt to Asset Ratio (DAR), Debt to Eqiity Ratio (DER), Return on Assets (ROA), Return on Equity (ROE), Operating Profit Margin (OPM) and Net Profit Margin (NPM).